Ionospheric total electron content: Spatial patterns of variability. Issue 10 (25th October 2016) - Lean, J. L.; Meier, R. R.; Picone, J. M.; Sassi, F.; Emmert, J. T.; Richards, P. G.
Abstract: The distinctive spatial patterns of the ionosphere's total electron content (TEC) response to solar, seasonal, diurnal, and geomagnetic influences are determined across the globe using a new statistical model constructed from 2‐hourly TEC observations from 1998 to 2015. The model combines representations of the physical solar EUV photon and geomagnetic activity drivers with solar‐modulated sinusoidal parameterizations of four seasonal cycles and solar‐modulated and seasonally modulated parameterizations of three diurnal cycles. The average absolute residual of the data‐model differences is 2.1 total electron content unit, 1 TECU = 10 16  el m −2 (TECU) (9%) and the root‐mean‐square error is 3.5 TECU (15%). Solar and geomagnetic variability, the semiannual oscillation and the diurnal and semidiurnal oscillations all impact TEC most at low magnetic latitudes where TEC itself maximizes, with differing degrees of longitudinal inhomogeneity. In contrast, the annual oscillation manifests primarily in the Southern Hemisphere with maximum amplitude over midlatitude South America, extending to higher southern latitudes in the vicinity of the Weddell Sea. Nighttime TEC levels in the vicinity of the Weddell Sea exceed daytime levels every year in Southern Hemisphere summer as a consequence of the modulation of the diurnal oscillations by the seasonal oscillations. The anomaly, which is present at all phases of the solar cycle, commences sooner and ends later under solar minimum conditions. The model minus data residuals maximize at tropical magnetic latitudes in four geographical regions similar to the ionosphere pattern generated by lower atmospheric meteorology. Enhanced residuals at northern midlatitudes during winter are consistent with an influence of atmospheric gravity waves. Key Points: Maximum TEC response to solar, SAO, diurnal, and geomagnetic influences is at low magnetic latitudes and to AO in SH Solar‐modulated seasonal oscillations cause Weddell Sea diurnal anomaly in SH summer, lasting longer at solar minima Evidence for lower atmosphere meteorologic influence on TEC in the EIA and at NH midlatitudes in winter